Diagnosis of A3 Pulley Injuries Using Ultrasound. - Schoeffl, Isabelle; Deeg, Johannes; Lutter, Christoph; Bayer, Thomas; Schöffl, Volker (Sportverletzung-Sportschaden, 2018)
RATIONALE AND OBJECTIVES: Pulley ruptures are the most common injuries in sport climbing. Ruptures of the A2 and A4 pulleys have been studied extensively, and ultrasound has proven to be a highly sensitive and specific tool for their diagnosis. However, the correct diagnosis of A3 pulley ruptures continues to be a challenge. Therefore, we investigated a novel approach to this pathology. MATERIAL AND METHODS: Eighteen fingers from nine different human cadavers were examined using high-resolution, dynamic ultrasound before and after being subjected to different combinations of singular and multiple iatrogenic pulley ruptures in a standardised fashion. Special attention was paid to the behaviour of the volar plate (VP) with respect to the proximal interphalangeal joint (PIP) and the flexor tendons before and after pulley rupture. RESULTS: Injuries to the A2 and A4 pulleys were diagnosed via ultrasound with sensitivities of 90 % and 94 % and specificities of 100 % and 97 %, respectively. A direct visualisation of the A3 pulley was achieved in 61 % of the fingers. The VP became significantly thicker and shorter during finger flexion as well as after A3 pulley rupture. The distance between tendon and VP became significantly more pronounced after A3 pulley rupture. For distances greater than 0.9 mm between VP and tendon, a sensitivity of 76 % and a specificity of 94 % were achieved for determining A3 pulley ruptures. CONCLUSION: The distance measurement between VP and tendon was found to be a valid indirect method for the diagnosis of A3 pulley ruptures. This approach is the first ultrasound method for accurately diagnosing A3 pulley ruptures.
EVALuna2:469505
Keywords: sport climbing; finger injury; volar plate; pulley

Different Effects of Foam Rolling on Passive Tissue Stiffness in Experienced and Nonexperienced Athletes - Mayer, Isabel; Hoppe, Matthias Wilhelm; Freiwald, Jürgen; Heiß, Rafael; Engelhardt, Martin; Grim, Casper; Lutter, Christoph; Hüttel, Moritz; Forst, Raimund; Hotfiel, Thilo (Journal of Sport Rehabilitation, 2019)
CONTEXT: Foam rolling (FR) has been developed into a popular intervention and has been established in various sports disciplines. However, its effects on target tissue, including changes in stiffness properties, are still poorly understood. OBJECTIVE: To investigate muscle-specific and connective tissue-specific responses after FR in recreational athletes with different FR experience. DESIGN: Case series. SETTING: Laboratory environment. PARTICIPANTS: The study was conducted with 40 participants, consisting of 20 experienced (EA) and 20 nonexperienced athletes (NEA). INTERVENTION: The FR intervention included 5 trials per 45 seconds of FR of the lateral thigh in the sagittal plane with 20 seconds of rest between each trial. MAIN OUTCOME MEASURES: Acoustic radiation force impulse elastosonography values, represented as shear wave velocity, were obtained under resting conditions (t0) and several times after FR exercise (0 min [t1], 30 min [t2], 6 h [t3], and 24 h [t4]). Data were assessed in superficial and deep muscle (vastus lateralis muscle; vastus intermedius muscle) and in connective tissue (iliotibial band). RESULTS: In EA, tissue stiffness of the iliotibial band revealed a significant decrease of 13.2% at t1 (P ≤ .01) and 12.1% at t3 (P = .02). In NEA, a 6.2% increase of stiffness was found at t1, which was not significantly different to baseline (P = .16). For both groups, no significant iliotibial band stiffness changes were found at further time points. Also, regarding muscle stiffness, no significant changes were detected at any time for EA and NEA (P > .05). CONCLUSIONS: This study demonstrates a significant short-term decrease of connective tissue stiffness in EA, which may have an impact on the biomechanical output of the connective tissue. Thus, FR effects on tissue stiffness depend on the athletes' experience in FR, and existing studies have to be interpreted cautiously in the context of the enrolled participants.
EVALuna2:209959